Bacteriological, inorganic and heavy metal evaluation of drinking water of the specified flood affected areas of Dir (Lower) Pakistan. Issue 30 (26th June 2016) - Zahoor, Muhammad; Ali Khan, Farhat; Azam, Muhammad
Abstract: In the year 2010, Pakistan was badly hit by devastating flood and about one-fifth of the total area of the country was under the flood water. In this study, an attempt was made to find out whether the portable water sources were still contaminated with various pollutants or not, after two years of the devastating flood. The samples were collected from selected areas of Dir Lower Khyber Pakhthoonkhwa Pakistan in 2012. Different physicochemical parameters like pH, EC, turbidity, alkalinity and hardness, , , F −1, Cl −1, Na, K, Ca, Mg, Cr, Ni, Fe and Pb were determined. The samples were also checked for the presence of pathogenic bacteria. The collected water samples were found contaminated with high level of nutritional metals, heavy metals (Cr, Ni, Fe, Pb) and pathogenic bacteria such as coliform, faecal coliform, E. coli, S. aureus .